FORMULATION AND PHYSICAL EVALUATION OF MICROEMULSION AND W/O/W MULTIPLE EMULSIONS DOSAGE FORMS WITH ALPHA ARBUTIN, LACTIC ACID, AND NIACINAMIDE AS SKIN-WHITENING COSMETICS - Surini, Silvia; Mellani, Tina (International Journal of Applied Pharmaceutics, 2017)
Objective: The present study aimed to formulate and determine the physical stability of microemulsion and W/O/W multiple emulsions, containing α arbutin, lactic acid, and niacinamide, as skin-whitening cosmetics. Methods: A skin lightening effect can also be obtained from lactic acid, which accelerates the turnover of pigmented cells in the epidermis, and from niacinamide, which inhibits the transfer of melanosomes from melanocytes to keratinocytes. These active ingredients were combined in microemulsion and W/O/W multiple emulsions dosage forms in various concentrations of Tween 80 as an emulsifier. An evaluation and physical stability test were carried out during 12 weeks of storage at 28±2°C, 4±2°C, and 40±2°C, as well as a cycling test. Results: The results showed that a microemulsion could be prepared in 25-35% of Tween 80 (surfactant) and 10% of ethanol (co-surfactant), and that it had globule sizes of 2.397-16.8 nm, a transparent, pseudoplastic flow, and was most stable in storage at 28±2°C. Microemulsion with 35% of Tween 80 was the most stable microemulsion formula because it had the smallest globule size, the most stable distribution profiles of globule sizes, and the highest viscosity. W/O/W multiple emulsions could formulated made with 2.5-4.5% of Tween 80 (external emulsifier) and 3% of Span 80 (internal emulsifier); these emulsions had a pseudoplastic-thixotropic flow and were most stable in storage at 28±2°C. Conclusions: The formulation of multiple emulsions with 2.5% of Tween 80 was the most stable formula, with a stable distribution profile of globule sizes during 8 weeks of storage at temperatures of 28±2°C, 4±2°C, and 40±2°C.